Building digital engagement through archipelagic horror narratives: The “wawak” community’s responses to Nadia Omara’s storytelling content - Nurlimah, Nila; Akmali, Resty Maulani; Herlina, Rita; Bin Idris, Awang (Islamic Communication Journal, 2025)
Horror narrative content on YouTube has developed into a space that fosters audience engagement and community identity. The Kisah Horror Wawak (KHW) program hosted by Nadia Omara demonstrates active involvement from the “Wawak” community in both enjoying and sharing horror stories. This can be seen in Nadia Omara’s achievement of 9.76 million subscribers and more than 2 million viewers. This study examines how the “Wawak” community responds in building engagement with Nadia Omara’s horror storytelling content. This research uses a case study approach. The findings show that Nadia Omara’s success in building viewer engagement is supported by several strategies: (1) a unique and interactive storytelling style, the use of an Acehnese dialect in narrating Indonesian horror stories, and the habit of addressing viewers as “Wawak”; (2) active feedback through likes, comments, expressions of gratitude during video openings, and cross-platform promotion; and (3) the diversity of Indonesian horror stories that effectively entertain viewers. In conclusion, the KHW program hosted by Nadia Omara has successfully built audience community engagement through a form of horror storytelling that is unique, interactive, and rooted in local cultural contexts. This study contributes by clarifying how digital engagement can be constructed through the integration of personal narratives, audience participation, and local cultural identity within new media environments. ***** Konten narasi horor di YouTube telah berkembang menjadi ruang interaksi yang menunjukkan engagement dan identitas komunitas audiens. Program Kisah Horror Wawak (KHW) yang dibawakan oleh Nadia Omara menampilkan keterlibatan aktif komunitas “Wawak” dalam menikmati sekaligus berbagi cerita horor. Hal ini terlihat dari keberhasilan Nadia Omara dalam meraih 9,76 juta subscriber dan lebih dari 2 juta penonton. Penelitian ini mengkaji bagaimana respon komunitas “Wawak” dalam membangun engagement terhadap konten storytelling horror Nadia Omara. Penelitian ini menggunakan pendekatan studi kasus. Penelitian ini menunjukkan, bahwa keberhasilan Nadia Omara dalam meraih viewers engagement didasarkan pada beberapa strategi yaitu; (1) cara ber-storytelling yang unik dan interaktif, penggunaan logat Aceh dalam bercerita kisah horor nusantara dan kebiasaan menyapa  “wawak” pada para viewers-nya, (2) aktif memberi feedback dalam bentuk pemberian simbol like, komentar dan ucapan terima kasih saat opening video, serta cross platform promotion, dan (3) keberagaman cerita horor Nusantara serta mampu menghibur viewers. Kesimpulannya, program KHW yang dibawakan oleh Nadia Omara berhasil membangun engagement komunitas audiens melalui storytelling horor yang unik dan interaktif dan berakar pada lokalitas. Studi ini berkontribusi dengan memperjelas bagaimana keterlibatan digital dapat dibangun melalui perpaduan narasi personal, partisipasi audiens, dan identitas budaya lokal di ruang media baru.